Identification of risk factors for supra-therapeutic vancomycin trough levels in ventilator-assisted critical care patients based on integrated modeling and multi-criteria decision analysis - Xi Cao; Bi-ting Zhu; Cai-peng Xie; Jing-yue Cai; Ding-guo Dong; Miao-ting Chen; Cheng-zhao Huang; Yong-chun Lin (PLoS ONE, 2025)
To explore the risk factors influencing vancomycin trough concentration (Cvg−min) overexposure in critically ill patients with mechanical ventilation and rank the factors, the medical records of 194 mechanically ventilated critically ill patients hospitalized from 12/10/2021–06/10/2024 were analyzed. Among 194 critically ill patients, 77.83% were male and 22.17% were female. Univariate analysis showed that oxygenation index (OI), activated partial thromboplastin time (APTT), urea nitrogen (UN), septic shock, heart disease, congestive heart failure (CHF), moderate/severe chronic kidney disease (CKD), etc. were statistically different (P < 0.05). And APTT, OI, CHF and moderate/severe CKD were statistically different in multivariate logistic regression (P < 0.05). The receiver operating characteristic (ROC) curve constructed for APTT and OI was 0.7779 (95% CI [0.708,0.848], P < 0.001), with a sensitivity and specificity were 72.99% and 71.93%, respectively. The consistency index (CI) and consistency ratio (CR) of analytic hierarchy process (AHP) was 0.0796 and 0.0885, respectively, which meets the consistency test standard. The contributions of APTT, OI, CHF and moderate to severe CKD to the overexposure of Cvg−min were 0.0584, 0.1899, 0.1614 and 0.5902, respectively. The overexposure rates of Cvg−min in patients with moderate/severe CKD and CHF were 95.12% and 95.23%, respectively. With regard to OI, when the cutoff value of OI was less than 245, the Cvg−min overexposure rate was 83%, otherwise, the overexposure rate was 60.97%. The risk factors for excessive exposure of Cvg−min in critically ill patients with mechanical ventilation were ranked as follows: moderate/severe CKD > OI > CHF > APTT.